2013
DOI: 10.1002/nav.21560
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic service rate control for a single-server queue with Markov-modulated arrivals

Abstract: Abstract:We consider the problem of service rate control of a single-server queueing system with a finite-state Markov-modulated Poisson arrival process. We show that the optimal service rate is nondecreasing in the number of customers in the system; higher congestion levels warrant higher service rates. On the contrary, however, we show that the optimal service rate is not necessarily monotone in the current arrival rate. If the modulating process satisfies a stochastic monotonicity property, the monotonicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…The paper [41] deals with similar questions by comparing this queue with an appropriate M/M/1 queue. Optimization of service rate for the case when arrival rate is a Markov process is studied in [26]. See also, a birthdeath process in random environment [13] and a Markov chain in Markov environment, studied in [12,16,33].…”
Section: 1mentioning
confidence: 99%
“…The paper [41] deals with similar questions by comparing this queue with an appropriate M/M/1 queue. Optimization of service rate for the case when arrival rate is a Markov process is studied in [26]. See also, a birthdeath process in random environment [13] and a Markov chain in Markov environment, studied in [12,16,33].…”
Section: 1mentioning
confidence: 99%
“…The customer arrival rate normalλi is constant but different for each system i. We want to allow the server to become faster when there are more customers waiting in queue, which is referred as the dynamic service rate control policy in the literature (eg, Kumar, Lewis, & Topaloglu, ). The service rate for customer m from system i is specified as boldμi+0.01×(Qm6), where Qm is random and represents the number of customers waiting in line when the mth customer just enters the server.…”
Section: Illustrative Examplesmentioning
confidence: 99%
“…The system responds to the fluctuating demand through dynamic pricing and inventory replenishment. Kumar et al (2013) analyze service facilities with exponentially distributed production times and seasonal demands. Using dynamic programming, they identify the optimal policy as a state-dependent production rate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We consider a policy π such that μ n,s = μ max for n < N 0 and μ n,s = 0 for n ≥ N 0 for all s ∈ S, where N 0 is a positive integer. Then using arguments similar to Proposition 2.2 of Kumar et al (2013), it can be shown that under the condition described in Equation (1), the Markov chain induced due to this policy is irreducible, ergodic in the state space (−∞, N 0 ] × S, and has finite long-run expected average cost. Note that we have validated Assumption 7 under finite upper bound of the net inventory level.…”
Section: A2 Proofs For Average Expected Cost Criterionmentioning
confidence: 99%